Bulgarian Intellectuals in the Mirror of Their Collective Public Positions (2005-2019) - Mihailova, Katia (UNWE Yearbook, 2020)
The paper presents results of content analyses of 69 public collective positions of Bulgarian intellectuals, published in the internet media in the period of 2005-2019. The research question is what the image of the Bulgarian intellectuals in the mirror of their public collective positions is. Theoretical roots of the research are in the sociology of intellectuals and sociology of interventions. It is built on the works on intellectuals and intellectual field of the classic sociologists from XX century, as well as their new millennium successors. This study poses a number of questions for further research.